Dignity in The Remains of the Day from the Lens of Ontology, Ethics, and Liberalism - Sareh Khosravi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
This study examines the concept of dignity in Kazuo Ishiguro’s The Remains of the Day, contrasting the universal, ontological notion of inherent dignity with the limited, class-based view held by the protagonist, Mr. Stevens. The study argues that Stevens' narrow understanding of dignity, rooted in his service to his employer (a Nazi sympathizer), leads him to engage in immoral actions. This analysis draws on Kant's focus on good will as the basis of moral behaviour, proposing that although Stevens demonstrates a significant sense of duty and follows rules closely, he lacks the essential moral consciousness necessary for genuinely ethical conduct. The protagonist’s actions, though ethically sound within his specific social context, are ultimately driven by a desire to maintain a rigid, hierarchical order. The research also analyzes Stevens' actions through the lens of John Rawls' liberalism, which emphasizes the influence of social institutions on individual values. The study concludes that Stevens' flawed definition of dignity serves as a tool to justify his service and evade personal responsibility. His reliance on a narrow notion of dignity allows him to rationalize his actions, even as they contradict a broader understanding of morality and human worth.